Impact of Tillage and Residue Management on Water and Thermal Regimes of a Sandy Loam Soil under Pigeonpea-Wheat Cropping System - Sanatan Pradhan, R.K. Tomar, U.K. Behera, A.R. Sharma, A. Paul and Debashis Chakraborty, Surajit Mondal, Anupam Das (Journal of the Indian Society of Soil Science, 2018)
Tillage and crop residue management are the most critical components of the cultivation, which significantlyaffect the soil-plant-water relations. Conservation tillage (CT) aims to improve soil condition and conservesoil water, although limited information is available on seasonal variation of soil water and temperatureunder cropping systems. A medium duration (6 years) experiment with different tillage and residuemanagement option on a sandy loam soil in pigeonpea-wheat cropping system was selected to monitor thechanges in soil structure through adoption of conservation agriculture (CA), and the subsequent impact onsoil water and thermal regimes over the growing period of wheat crop. Treatments were: conventionaltillage with incorporation of previous crop residue (CT+R); conventional tillage with residue removal (CTR);no-tillage with residue retained over surface as mulch (NT+R); and no-tillage with residue removed(NT-R). The impact was quantified in terms of change in basic soil physical parameters viz., bulk density(BD), penetration resistance (as Cone Index, CI) and porosity, and their effect on soil water dynamics, andseasonal and diurnal soil temperature. At the initial growth stages (9 to 51 DAS), NT+R and NT-Rrecorded 5-10 per cent higher BD at 0-10 cm layer, but was comparable with CT+R and CT-R at the laterstages. Soil pore (30 μm) and meso- (5-30 μm) pore volumes had marginal differences.A sub-surface (10-20 cm) hard layer (CI 1.7-1.9 MPa) was omnipresent, although omission of tillage resultedin marginal reduction in CI at this layer. Marginally higher macro-pores in NT systems caused higher initialrate of infiltration and the cumulative infiltration. Throughout the growing season of wheat, NT+R retainedhigher soil water than other tillage-residue combinations [17% (0 to 48), 11% (-5 to 32), and 14% (-2 to 36),higher compared to NT-R, CT+R and CT-R]. Soil water content in NT+R was also higher by 20% (-5 to41) before irrigation cycles. Similarly, soil temperature was the most regular in NT+R, even at 3 cm depthdue to the presence of surface residue and higher amount of soil water. The difference between temperaturesat 10 am and 3:30 pm was 2.9 (0.2-6.3) °C in NT+R, compared to 3.8 (0.2-7) °C in NT-R, 4 (0.8-8) °C inCT+R, and 3.1 (0.7-5.5) °C in CT-R. Therefore, role of tillage and crop residues in modifying soil physicalenvironment and maintaining better soil water and thermal conditions have been clearly documented.